2021
DOI: 10.1152/japplphysiol.00554.2020
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening of the extracellular matrix is a sufficient condition for airway hyperreactivity

Abstract: The current therapeutic approach to asthma focuses exclusively on targeting inflammation and reducing airway smooth muscle force to prevent the recurrence of symptoms. However, even when inflammation is brought under control, airways in an asthmatic can still hyper-constrict when exposed to a low dose of agonist. This suggests that there are mechanisms at play that are likely triggered by inflammation and eventually become self-sustaining so that even when airway inflammation is brought back under control, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Aligned with our findings, Liao et al reported that Piezo-1 activation by Yoda1 induces contraction of human pulmonary arterial vSMCs and dose-dependent vasoconstriction of rat intrapulmonary arteries, due to intracellular Ca 2+ increase 67 . These observations fuel maturing evidence of augmented calcium signaling 68 and contractility 69,70 in SMCs embedded within a stiff matrix. Note, Retailleau et al reported that Piezo-1 signaling promotes thickening of the murine caudal artery by stimulating the Ca 2+ -dependent catalytic activity of transglutaminases 71 and tissue transglutaminase contributes to vascular stiffening during aging [72][73][74] .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Aligned with our findings, Liao et al reported that Piezo-1 activation by Yoda1 induces contraction of human pulmonary arterial vSMCs and dose-dependent vasoconstriction of rat intrapulmonary arteries, due to intracellular Ca 2+ increase 67 . These observations fuel maturing evidence of augmented calcium signaling 68 and contractility 69,70 in SMCs embedded within a stiff matrix. Note, Retailleau et al reported that Piezo-1 signaling promotes thickening of the murine caudal artery by stimulating the Ca 2+ -dependent catalytic activity of transglutaminases 71 and tissue transglutaminase contributes to vascular stiffening during aging [72][73][74] .…”
Section: Discussionsupporting
confidence: 58%
“…reported that Piezo-1 activation by Yoda1 induces contraction of human pulmonary arterial vSMCs and dose-dependent vasoconstriction of rat intrapulmonary arteries, due to intracellular Ca 2+ increase 67 . These observations fuel maturing evidence of augmented calcium signaling 68 and contractility 69,70 in SMCs embedded within a stiff matrix. Note, Retailleau et al .…”
Section: Discussionsupporting
confidence: 57%
“…On shorter timescales Stasiak et al (2020) show that ECM regulates agonistinduced calcium oscillations in ASM cells; calcium responses in healthy donor ASM cells and stiffened underlying ECM were consistent with responses that would be expected with significantly higher agonist dose. Similarly, interactions between the ASM and a stiffer ECM environment have been shown to lead to increased ASM contractility (Polio et al, 2019) and enough to lead to hyperresponsiveness (Jamieson et al, 2021). All of the above are characteristic features of asthma, suggesting that detailed models of both acute bronchoconstriction and long-term remodelling designed to investigate mechanopharmacological therapies will benefit from the inclusion of the mechanics and regulatory aspects of ECM in airways.…”
Section: Discussionmentioning
confidence: 99%
“…The stiffness of the ECM is a major determinant for functional responses of cells within this environment [89]. JAMIESON et al [90] recently illustrated that the stiffness of collagen fibres governed the propensity of an airway to contract in the presence of a stimulus. Cross-linking of collagen fibres, reflecting the remodelled ECM found in an asthmatic airway, resulted in a stiffer airway wall that constricted to a greater degree and at a faster rate.…”
Section: Ecm Biomechanics Impact Of Ecm Biomechanics In Terms Of Cell...mentioning
confidence: 99%